The multifunctional role of Pseudomonas spp. as plant growth-promoting rhizobacteria (PGPR): A sustainable approach to biofertilization and plant health - Shah Ahmed Reza; Mingzhao Han; Md Kamal Uddin; Susilawati Binti Kasim; Ali Tan Kee Zuan; Farooq Anwar; Sriharan Raguraj (Universitas Sebelas Maret, 2026)
Sustainable agriculture relies on maintaining healthy, ecologically balanced soil. The excessive use of chemical fertilizers has resulted in declining soil fertility, biodiversity loss, and structural degradation. In particular, the use of biofertilizers containing microbial inoculants that enhance plant growth and soil health offers a promising alternative by improving nutrient availability, suppressing pathogens, and restoring soil ecosystems. Studies have shown that rhizosphere microbes can enhance plant growth and control diseases by producing phytohormones and aiding nutrient uptake. Many bacterial genera can be used as biofertilizers, including nitrogen-fixers, phosphorus-solubilizers, potassium-solubilizers (K-solubilizers), and others. Among the diverse plant growth-promoting rhizobacteria (PGPR), species within the Pseudomonas genus have emerged as promising candidates due to their exceptional versatility and resilience. Pseudomonas spp. exhibits a wide array of plant growth-promoting traits, including atmospheric nitrogen fixation, solubilization of phosphorus and potassium, and the secretion of phytohormones such as indole-3-acetic acid (IAA) and gluconic acid. By systematically linking their metabolic traits to specific soil health and crop productivity outcomes, this review provides new insights into their potential application in sustainable and climate-resilient agriculture. Several Pseudomonas species have been extensively utilized as biofertilizers due to their multifunctional traits, adaptability to a wide range of soil environments, and capacity to enhance plant health under both biotic and abiotic stress conditions. The primary objective of this review is to present a comprehensive overview of biofertilizer mechanisms and the functional roles of Pseudomonas spp., including selected strains known to improve plant growth and soil fertility.